Adaptation of Curriculum and Technology in Responding to the Flow of Globalization: Case Study of PPM Al-Azhar Muncar Banyuwangi - Muhammad Alif Al Raihan; Anisa Ananda; Muthmainah; Muhammad Reza Syahbudi; Arga Sabda Wiguna (Journal of Research in Islamic Education, 2025)
This study aims to analyze the adaptation of curriculum and technology at the Al-Azhar Muncar Banyuwangi Modern Islamic Boarding School in responding to the flow of globalization. As an Islamic educational institution that seeks to maintain traditional values ​​while being relevant to the development of the times, this Islamic boarding school makes various adjustments in its curriculum to integrate general and religious knowledge comprehensively. This type of research is qualitative descriptive, namely a method that seeks to describe and explain phenomena in depth based on data obtained in the field. The results found that the Al-Azhar Muncar Modern Islamic Boarding School strategically faces globalization by combining the national and Islamic boarding school curriculum, as well as optimizing technology and character development of students and implementing a cashless payment system for efficiency and security. Despite the challenges of limited time access to technology, Al-Azhar Muncar continues to make maximum efforts with periodic teacher training and encouraging students to create positive content and participate in various extracurricular activities.